Thomas, George Henry (Tufts Archival Research Center, 2008)
2.5 x 4.25. "Thomas, George Henry 1816-1870; Major general (Union Army) 1865." Produced by: Joseph Ward, 125 Washington Street, Boston. These dates are approximate.